Economic evaluation of posaconazole versus standard azole therapy as prophylaxis against invasive fungal infections in patients with prolonged neutropenia in Canada - Tahami Monfared, Amir A (Pulsus Group Inc, 2012)
INTRODUCTION: Posaconazole prophylaxis in high-risk neutropenic patients prevents invasive fungal infection (IFI). An economic model was used to assess the cost effectiveness of posaconazole from a Canadian health care system perspective. METHODS: A decision-analytic model was developed based on data from a randomized trial comparing posaconazole with standard azole (fluconazole or itraconazole) therapy. The model was extrapolated to a lifetime horizon using one-month Markov cycles; lifetime survival was specific to the underlying disease. Drug and treatment costs associated with IFI were estimated using published literature. The model was used to estimate total costs, IFIs avoided, life-years gained and the incremental cost-effectiveness ratio of posaconazole versus standard azole therapy, in 2007 Canadian dollars. RESULTS: Based on the clinical trial data, posaconazole was associated with fewer cases of IFI (0.05 versus 0.11; P=0.003), increased life-years (2.52 years versus 2.43 years) and slightly lower costs ($6,601 versus $7,045) per patient relative to standard azole therapy over a lifetime horizon. Higher acquisition costs for posaconazole were offset by IFI-associated inpatient costs for those prophylaxed with standard azoles. Probabilistic sensitivity analysis indicated a 59% probability that posaconazole was cost-saving versus standard azole therapy and a 96% probability that the incremental cost-effectiveness ratio for posaconazole was at or below the $50,000 per life-year saved threshold. DISCUSSION: In Canada, posaconazole appears to be cost-saving relative to standard azole therapy in IFI prevention among high-risk neutropenic patients.